Utilization of Boxes for Pesticide Storage in Sri Lanka. Issue 2 (3rd April 2017) - Pieris, Ravi; Weerasinghe, Manjula; Abeywickrama, Tharaka; Manuweera, Gamini; Eddleston, Michael; Dawson, Andrew; Konradsen, Flemming
ABSTRACT: Pesticide self-poisoning is now considered one of the two most common methods of suicide worldwide. Encouraging safe storage of pesticides is one particular approach aimed at reducing pesticide self-poisoning. CropLife Sri Lanka (the local association of pesticide manufacturers), with the aid of the Department of Agriculture, distributed lockable in-house pesticide storage boxes free of charge to a farming community in a rural district of Sri Lanka. Padlocks were not provided with the boxes. These storage boxes were distributed to the farmers without prior education. The authors carried out a cross-sectional follow-up survey to assess the usage of boxes at 7 months after distribution. In an inspection of a sample of 239 box recipients' households, 142 households stored pesticides in the provided box at the time of survey. Among them, only 42 (42/142, 29.65%) households had locked the box; the remaining households (100/142, 70.4%) had not locked the box. A simple hand over of in-house pesticide storage boxes without awareness/education results in poor use of boxes. Additionally, providing in-house storage boxes may encourage farmers to store pesticides in and around houses and, if they are not locked, may lead to unplanned adverse effects.